ANALYZING THE AMAZON SUCCESS STRATEGIES - Sadq, Zana Majed; Sabir, Hawre Nuraddin; Hama Saeed, Vian Sulaiman (Journal of process management and new technologies, 2018)
This paper aims to present the Amazon success strategies. Since the objective of the Company is to become the best place to buy, find and discover any product or service available online. Amazon.com will continue to enhance and broaden its brand, customer base and electronic commerce expertise with the goal of creating customers' preferred online shopping destination, in the United States and around the world.